The transfer cost of parenthood in Europe - Rob́ert Ivań Gaĺ; Maŕton Medgyesi; Pieter Vanhuysse (Hungarian Demographic Research Institute, 2020)
What are the net resource transfer burdens of working-age parents and non-parents in Europe? We estimate all cash, in-kind, and time transfers of the market economy and the household economy, through both public and familial channels, for fourteen European countries in the early 2000s. We advance National Transfer Accounts methodology by splitting up macro-aggregates into three groups: parents, non-parents living in childless households and non-parents cohabiting with children. We find that non-parents contribute almost exclusively to public transfers in net terms, somewhat more than parents do. But parents provide, in addition, a still larger amount of familial transfers. As a result, parents contribute on average 1.8 times as many net transfers as non-parents do, overall. Especially in view of the public good nature of children and contemporary rates of childlessness in Europe, this asymmetric transfer burden carries multiple implications for debates on public policy and a just society.
Keywords: 300; National Transfer Accounts; parenthood; cost of children; intergenerational transfers; children as public goods; distributional equity; pronatalist policy